Body Height of Children with Bronchial Asthma of Various Severities. (26th July 2017) - Eliseeva, Tatiana I.; Geppe, Natalia A.; Tush, Elena V.; Khaletskaya, Olga V.; Balabolkin, Ivan I.; Bulgakova, Vilya A.; Kubysheva, Nailya I.; Ignatov, Stanislav K.
Abstract : Influence of bronchial asthma (BA) severity on physical development in children patients was evaluated in comparison with healthy population. Materials and Methods . 1042 children and adolescents (768 boys) with atopic BA were evaluated. All children underwent standard examination in a clinical setting, including anthropometry. The control group included 875 healthy children of a comparable age (423 boys). Results . The fraction of patients with the normal, lower, and increased height among the whole group of patients with BA is close to the corresponding values in the healthy population (χ 2 = 3.32, p = 0.65 ). The fraction of BA patients with the reduced physical development is increased monotonically and significantly when the BA severity increases: healthy group, 8.2% (72/875), BA intermittent, 4.2% (6/144), BA mild persistent 9% (47/520), BA moderate persistent, 11.7% (36/308), and BA severe persistent, 24.3% (17/70) (χ 2 = 45.6, p = 0, 0009 ). Conclusion . The fraction of the children with the reduced height is increased monotonically and significantly in the groups of increasing BA severities. At the same time, the fraction of such children in groups of intermittent and mild persistent BA practically does not differ from the conditionally healthy peers.